Sampling technique affects the population structure assessments of fiddler crab Minuca vocator (Herbst, 1804) (Ocypodidae: Gelasiminae) - Delevati Colpo, Karine (2016)
We examined how the sampling technique can affect the evaluation of Minuca vocator (Herbst, 1804) population structure. We used two sampling procedures: catch-per-unit-effort (CPUE) and quadrat technique (QT). Body size, size?frequency distribution, population density, juvenile recruitment rates, proportion of ovigerous females and sex ratio were compared between the sampling procedures. QT allowed us to estimate and compare crab and burrow densities. CPUE sampled both adult crabs and the largest crabs more frequently, whereas QT recorded a greater proportion of smaller crabs. CPUE underestimated the size of M. vocator populations, while density estimates obtained with QT were accurate. The proportion of juveniles was higher with QT than with CPUE, suggesting that recruitment rates estimated by QT were more suitable. The sampling effort provided by CPUE was more efficient for obtaining ovigerous-dependent information than QT. Both sampling techniques showed a predominance of males in all three M. vocator populations. The population density estimation based on burrows overestimated the natural density of M. vocator in all mangroves. Our results suggest that neither CPUE nor QT individually were accurate sampling techniques, but together provided reliable assessments of fiddler crab populations.